2010
DOI: 10.1111/j.1945-5100.2010.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pyridine treatment on phase Q: Orgueil and Allende

Abstract: Abstract-Marrocchi et al. (2005) reported that low-temperature fractions of heavy noble gases were largely removed upon pyridine treatment of the Orgueil CI meteorite. As pyridine is known to induce the swelling of the macromolecular network of organic matter, they concluded that the low-temperature phase Q is macromolecular organic carbon. However, Busemann et al. (2008) showed that pyridine had no significant effect on the noble gas contents for other very primitive meteorites, such as CM and CR. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Matsuda et al. () indicated that loss of Q‐gases was only the case for Orgueil and that it was due to the loss of some kind of organic matter that formed and adsorbed the fractionated Q‐ and HL gases during aqueous alteration of Orgueil's parent body. However, Spring et al.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuda et al. () indicated that loss of Q‐gases was only the case for Orgueil and that it was due to the loss of some kind of organic matter that formed and adsorbed the fractionated Q‐ and HL gases during aqueous alteration of Orgueil's parent body. However, Spring et al.…”
Section: Introductionmentioning
confidence: 99%
“…We also used CS 2 to remove elemental sulfur during the chemical treatment. [8,9] We investigated the effect of laser-induced heating on Raman peak positions, FWHMs, and intensity ratios of G and D bands for this sample.…”
Section: Methodsmentioning
confidence: 99%
“…[5] G-peak positions also increase with increasing degree of crystallinity. [6,10] The pyridine treatment did not affect the carbon structure [8] , but the acid leaching likely affected it. [9] Thus Raman spectroscopic parameters are good indicators for the metamorphism of meteorites, and their precise measurements are very important.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations